An alternative surgical approach for the combined treatment of pectus excavatum and acute aortic dissection type-A in Marfan syndrome - Schwill, Simon; Kallenbach, Klaus; Beller, Carsten J.; Karck, Matthias (Interactive cardiovascular and thoracic surgery, 2011)
Abstract. Acute aortic dissection type-A (AADA) is a life-threatening condition especially in patients with Marfan syndrome (MFS) simultaneously suffering from